Expanding the phenotypic spectrum of variants in PDE4D/PRKAR1A: from acrodysostosis to acroscyphodysplasia. (November 2018) - Michot, Caroline; Goff, Carine; Blair, Edward; Blanchet, Patricia; Capri, Yline; Gilbert-Dussardier, Brigitte; Goldenberg, Alice; Henderson, Alex; Isidor, Bertrand; Kayserili, Hulya; Kinning, Esther; Merrer, Martine; et al.
Abstract Acrodysostosis (MIM 101800) is a dominantly inherited condition associating (1) skeletal features (short stature, facial dysostosis, and brachydactyly with cone-shaped epiphyses), (2) resistance to hormones and (3) possible intellectual disability. Acroscyphodysplasia (MIM 250215) is characterized by growth retardation, brachydactyly, and knee epiphyses embedded in cup-shaped metaphyses. We and others have identifiedPDE4D orPRKAR1A variants in acrodysostosis;PDE4D variants have been reported in three cases of acroscyphodysplasia. Our study aimed at reviewing the clinical and molecular findings in a cohort of 27 acrodysostosis and 5 acroscyphodysplasia cases. Among the acrodysostosis cases, we identified 9 heterozygous de novoPRKAR1A variants and 11 heterozygousPDE4D variants. The 7 patients without variants presented with symptoms of acrodysostosis (brachydactyly and cone-shaped epiphyses), but none had the characteristic facial dysostosis. In the acroscyphodysplasia cases, we identified 2PDE4D variants. For 2 of the 3 negative cases, medical records revealed early severe infection, which has been described in some reports of acroscyphodysplasia. Subdividing our series of acrodysostosis based on the disease-causing gene, we confirmed genotype–phenotype correlations. Hormone resistance was consistently observed in patients carryingPRKAR1A variants, whereas no hormone resistance was observed in 9 patients withPDE4D variants. All patients withPDE4D variants shared characteristic facial features (midface hypoplasia with nasal hypoplasia) and some degree of intellectual disability. Our findings ofPDE4D variants in two cases of acroscyphodysplasia support thatPDE4D may be responsible for this severe skeletal dysplasia. We eventually emphasize the importance of some specific assessments in the long-term follow up, including cardiovascular and thromboembolic risk factors.